2008
DOI: 10.1111/j.1742-6723.2008.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated preparedness of Australian prevocational hospital doctors for emergencies

Abstract: Objective:To determine perceived preparedness of Australian hospital-based prevocational doctors for resuscitation skills and management of emergencies, and to identify differences between doctors who perceive themselves well prepared and those who perceive themselves poorly prepared for emergencies, in demographics and exposure to desired learning methods. Methods:Questionnaire consisting of a mix of graded Likert scales and free-text answers distributed to 36 Australian hospitals for secondary distribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Feedback of superiors, as well as living without a partner did indeed turn out to be associated with the feeling of preparedness, demonstrating the complex interactions which have to be considered when using self-assessments. Feedback was also identified as influencing factor on preparedness by other authors [29], stressing the importance and the benefit of the direct interaction between superiors and junior doctors, e. g. during "bedside teaching". Nevertheless, the inclusion of the above mentioned confounders did not alter the effect of deficits in the three identified core competencies on the feeling of preparedness, which underlines their independent influence.…”
Section: Discussionmentioning
confidence: 97%
“…Feedback of superiors, as well as living without a partner did indeed turn out to be associated with the feeling of preparedness, demonstrating the complex interactions which have to be considered when using self-assessments. Feedback was also identified as influencing factor on preparedness by other authors [29], stressing the importance and the benefit of the direct interaction between superiors and junior doctors, e. g. during "bedside teaching". Nevertheless, the inclusion of the above mentioned confounders did not alter the effect of deficits in the three identified core competencies on the feeling of preparedness, which underlines their independent influence.…”
Section: Discussionmentioning
confidence: 97%
“…The results of program evaluation indicated that the workshops’ processes and format have been valued by students, have enhanced student ability and preparedness to perform several of the procedural skills and also increased the amount of clinical experience they obtained. While relying on self-ratings of preparedness as a key evaluation measure may be a limitation, others have shown a link between poor perceived preparedness and limited exposure to clinical experience 25. Additionally, while students are supervised when performing procedures, introducing structured summative assessment has proved difficult, thus limiting outcome evaluation of the program.…”
Section: Discussionmentioning
confidence: 99%
“…A structured interview by telephone following consent of individual doctors was used to maximize response rate. This method was chosen over questionnaire methodology that we have found, in previous studies to yield a low response rate with this participant type 8–10 …”
Section: Methodsmentioning
confidence: 99%
“…This method was chosen over questionnaire methodology that we have found, in previous studies to yield a low response rate with this participant type. [8][9][10] For the larger Australian States, participants were drawn from a stratified sample of two city, two metropolitan and two provincial hospitals of each State/ Territory. Hospitals were selected based on the advice of the relevant postgraduate medical councils who were asked to nominate hospitals with ED and prevocational doctors 'representative' of the state for each category (city, metropolitan, provincial).…”
Section: Nationwide Studymentioning
confidence: 99%